Trade regionalism in the Asia-Pacific - Kawai, Masahiro, 1947-; Basu Das, Sanchita (ISEAS Publishing, 2016)
Asia has witnessed a proliferation of free trade agreements (FTAs) since the turn of the millennium. The first regional agreement -- the ASEAN FTA -- was transformed into the ASEAN Economic Community at the end of 2015. In the meantime, ASEAN forged five ASEAN+1 FTAs and began to negotiate a sixteen-member Regional Comprehensive Economic Partnership (RCEP) Agreement. In parallel, the U.S.-led Trans-Pacific Partnership (TPP), supporting U.S. foreign policy of "Pivot to Asia", was broadly agreed in October 2015. The RCEP and the TPP are accompanied by other mega-regional integration processes developing elsewhere in the world, including the Transatlantic Trade and Investment Partnership for the European Union and the United States, and the Pacific Alliance among four Latin American member states. Meanwhile, APEC is also striving to meet its Bogor Goal targets and create a Free Trade Area of the Asia-Pacific. Each of these mega-regionals aims to achieve greater trade and investment liberalization and facilitation and more harmonized trade and investment rules so that all member economies can participate in the global value chain of production. Instead of undermining, these regional exercises can be building blocks for a more liberal global trading system supported by the World Trade Organization. This book ruminates on these regional agreements, their economic and strategic rationales and challenges during negotiations and afterwards. The book brings together eminent scholars and experts to deepen our understanding of the complex nature of the mega-regional trade agreements and their implications. It is useful both for the academic and research community and for policymakers who focus on trade and economic cooperation issues